Capitalist Community in Tourism Development: Cultural Study Perspective - Dewa Putu Oka Prasiasa (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2022)
The study of capitalist society in tourism development based on the perspective of cultural studies is more emphasized on the relationship between politics and tourism, especially in terms of how tourism can change the composition of power and values in a Tourist Destination Area and vice versa. This research is a literature review research with qualitative descriptive analysis. Based on the results of the analysis of literature documents, this study finds the pattern of tourism development and its processes are the answers to conflicting values and interests; tourism can change the composition of power and values in a tourist destination in the form of domination as the exercise of power; tourism grows and develops in the midst of political changes that are strongly influenced by space and time; the study of tourism politics has presented three key players in tourism development, namely the state, society and market; capitalization and commodification arise as a result of the globalization of the tourism market or as a result of the internationalization of tourism; the placement of tourism in the capitalist space as a consequence of tourism politics will talk about who gets what, where it is obtained, and how to get it; and in studying tourism politics, it is necessary to know the political theory and political values that underlie public policy decisions, both explicitly and implicitly.